2021
DOI: 10.3389/fcell.2021.783617
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Pancreatic Stellate Cells Are Powerful Contributors to the Malignant Progression of Pancreatic Cancer

Abstract: Pancreatic cancer is associated with highly malignant tumors and poor prognosis due to strong therapeutic resistance. Accumulating evidence shows that activated pancreatic stellate cells (PSC) play an important role in the malignant progression of pancreatic cancer. In recent years, the rapid development of single-cell sequencing technology has facilitated the analysis of PSC population heterogeneity, allowing for the elucidation of the relationship between different subsets of cells with tumor development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…Previous studies have shown the cancer-promoting roles of PSCs [ 5 ]. For example, interleukin-6 secreted from PSCs promotes cell proliferation, stemness, and drug resistance of pancreatic cancer cells [ 14 ]. Xu et al [ 50 ] reported that PSCs promote the epithelial–mesenchymal transition and drug resistance of pancreatic cancer cells via paracrine hepatocyte growth factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown the cancer-promoting roles of PSCs [ 5 ]. For example, interleukin-6 secreted from PSCs promotes cell proliferation, stemness, and drug resistance of pancreatic cancer cells [ 14 ]. Xu et al [ 50 ] reported that PSCs promote the epithelial–mesenchymal transition and drug resistance of pancreatic cancer cells via paracrine hepatocyte growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the inhibitory effects of PSCs on pancreatic cancer have been reported [ 15 , 16 ]. The development of therapies targeting PSCs requires consideration of their heterogeneity [ 6 , 14 ]. Our study implies that senescent PSCs, which secrete various SASP factors despite having low α-SMA expression and anti-fibrotic effects, have features that are different from those of quiescent and activated PSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, cancer-promoting subpopulations of PSCs also have been identified. Interestingly, these PSCs are further divided into myofibroblastic and inflammatory subtypes, which produce collagen fibers and inflammatory cytokines, respectively ( Zhang et al, 2021 ). These studies highlighted the heterogeneity of PSCs, cancer-promoting and cancer-inhibiting roles, which should be taken into consideration for therapeutic intervention.…”
mentioning
confidence: 99%